Function of Protein S-Palmitoylation in Immunity and Immune-Related Diseases - Zhang, Yuqi; Qin, Ziran; Sun, Wenhuan; Chu, Feng; Zhou, Fangfang (Frontiers in Immunology, 2021)
Protein S-palmitoylation is a covalent and reversible lipid modification that specifically targets cysteine residues within many eukaryotic proteins. In mammalian cells, the ubiquitous palmitoyltransferases (PATs) and serine hydrolases, including acyl protein thioesterases (APTs), catalyze the addition and removal of palmitate, respectively. The attachment of palmitoyl groups alters the membrane affinity of the substrate protein changing its subcellular localization, stability, and protein-protein interactions. Forty years of research has led to the understanding of the role of protein palmitoylation in significantly regulating protein function in a variety of biological processes. Recent global profiling of immune cells has identified a large body of S-palmitoylated immunity-associated proteins. Localization of many immune molecules to the cellular membrane is required for the proper activation of innate and adaptive immune signaling. Emerging evidence has unveiled the crucial roles that palmitoylation plays to immune function, especially in partitioning immune signaling proteins to the membrane as well as to lipid rafts. More importantly, aberrant PAT activity and fluctuations in palmitoylation levels are strongly correlated with human immunologic diseases, such as sensory incompetence or over-response to pathogens. Therefore, targeting palmitoylation is a novel therapeutic approach for treating human immunologic diseases. In this review, we discuss the role that palmitoylation plays in both immunity and immunologic diseases as well as the significant potential of targeting palmitoylation in disease treatment.